Se & N co-doped carbon dots for high-performance fluorescence imaging agent of angiography. Issue 25 (6th June 2017) - Qu, Dan; Miao, Xiang; Wang, Xintong; Nie, Chuang; Li, Yuxin; Luo, Ling; Sun, Zaicheng
Abstract : Both long wavelength excitation and emission are highly desired for fluorescent carbon dots in bio-related applications. Abstract : Both long wavelength excitation and emission are highly desired for fluorescent carbon dots in bio-related applications. According to semiconductor theory, heteroatom doping is an effective way to tune the band gap of a semiconductor. In this work, we developed an exceedingly simple and mild one-pot method to synthesize selenium and nitrogen co-doped carbon dots (Se&N-CDs) by using low cost citric acid, ethane diamine and selenium powder as the starting materials. After doping the Se element into N-CDs, the absorption of Se&N-CDs was expanded from UV to the visible light region (∼497 nm). More important is that the Se&N-CDs show a strong green light emission with a high quantum yield of ∼52%, attributed to the new Se-state introduced in the Se&N-CDs due to the low electronegativity of Se. Furthermore, we successfully demonstrate that Se&N-CDs have an excellent performance as a dye for fluorescein fundus angiography (FFA). After injection, a clear vascular image in the retina and detailed images of the capillary bed were exhibited in the FFA image. This will provide a great advantage for bio-imaging and diagnosis.